Does inequality erode political trust? - Bienstman, Simon (Frontiers in Political Science, 2023)
A long-standing argument in the political sciences holds that high levels of inequality are incompatible with democracy. Although a number of studies have by now investigated whether income inequality endangers democratic consolidation and stability through corroding popular support, the findings remain inconclusive. This study provides new evidence for a sociotropic effect of macroeconomic income inequality on trust in the institutions of representative democracy by making use of the random effects within between specification in multilevel models for data from 28 European democracies over a period of 16 years. The findings show that both long-standing differences in income inequality between countries and changes in inequality within countries over time are negatively related to trust in institutions. While the spirit-level thesis states that this effect should be more pronounced among rich democracies, the findings show that the effect of inequality is stronger in countries that are less affluent. Further analyses on whether the social-psychological mechanism proposed by the spirit-level thesis mediates the effect of inequality on trust document a partial transmission via status concerns and social trust. However, the study suggests that income inequality primarily influences trust in institutions through evaluation-based processes as captured by economic evaluations.